Assembly and comparative analysis of the complete mitochondrial genome of Indocalamus longiauritus - Liu, Shinan; Zhang, Yinuo; Li, Lijie; Huang, Dayong; Qin, Yonghua (Frontiers in Plant Science, 2025)
Indocalamus longiauritus, as a dwarf bamboo holds the ecological and economic significance. Although earlier studies have successfully elucidated its chloroplast (cp) genome, the complete mitochondrial (mt) genome still is uncovered. This study undertook the sequencing, assembly, and comprehensive analysis of the complete mt genome of I. longiauritus. Based on the findings, the mt genome contained one circular and two linear contigs with the total length of 491,541bp. Totally, 59 genes were identified, which included 37 protein-coding genes (PCGs), 3 rRNA genes and 19 tRNA genes. In addition, 119 SSRs and 234 dispersed repeats were discovered. We discovered 602 RNA editing sites, with a striking 78.9% of them involving the conversion of hydrophilic amino acid to hydrophobic ones. Furthermore, in the I. longiauritus mt genome, 12 genes included 8 PCGs (petB, psbH, psbN, atpE, ndhJ, rps4, psaB, and ndhI) and 4 tRNA genes (trnM-CAU, trnV-UAC, trnF-GAA, and trnS-GGA) were found to transfer from the cp genome. Phylogenetic analysis showed a close genetic relationship of I. longiauritus with the species Fargesia qinlingensis and I. tessellatus. Collinearity analysis suggested that significant rearrangements existed in the mt genome of I. longiauritus. Selection pressure analysis revealed that more than half of PCGs had Ka/Ks values less than 1. Obviously, certain genes including rpl2, rpl5, rpl10, rpl14, rps2, rps11, rps12, rps14, rps19, and sdh4 were absent in the mt genomes of I. longiauritus and nine relative Poeceae species. Interestingly, the rpl14 gene was uniquely present in the mt genome of I. longiauritus. This study provides a significant genetic resource for the Bambusoideae family, which will facilitate further investigations in the molecular diversity and genetic evolution of bamboos.